О свойствах блоков членов ряда ∑1/k sinkx - Теляковский, С.А. (Український математичний журнал, 2012)
Дослiджено, на якi блоки можна розбити ряд ∑1\k sinkx, щоб сума ряду iз модулiв цих блокiв належала просторам Lp[0,π] або просторам Lp[0,π] з вагою x^−γ,γ<1. We analyze the possibility of decomposition of the series ∑1\k sinkx in blocks such that the sum of the series formed by the moduli of these blocks belongs to the spaces L p [0 π] or to the spaces L p [0 π] with weight x^−γ,γ<1.